Ultrasensitive triboelectric nanogenerator for weak ambient energy with rational unipolar stacking structure and low-loss power management. (November 2017) - Zhao, Zhizhen; Liu, Junjie; Wang, Zhenhai; Liu, Zhaoxian; Zhu, Wenqing; Xia, Huarong; Yang, Tian; He, Fang; Wu, Yanbing; Fu, Xiuli; Peng, Lian-Mao; Wei, Xiaoding; et al.
Abstract: Higher requirements have been put forward for self-powered systems operated with weak energy in the environment. Sensitivity, efficiency and power management design of the energy harvesting module play key roles on the sustainability of the system. In this work, we present an ultrasensitive triboelectric nanogenerator (TENG) with Cu coated fluorinated ethylene propylene films stacked in a unipolar manner and suspended by springs. Triboelectrification and electrostatic induction take place between every adjacent film surfaces, during which transferred charges are increased by at least 50%, leading to an increased efficiency. Also, the reduced framework weight makes soft spring can be adopted for greatly improved sensitivity. Depending on the investigation of mechanical motion in the system, TENG's energy harvesting efficiency is boosted by bringing down the moment of inertia. The linear region characteristic of an n-type junction field-effect transistor is utilized for a low-loss power management design with greatly reduced power consumption and start-up time for superior weak energy harvesting applications. Ultrasensitive and high efficient energy harvester with low-loss power management demonstrated in this work promises an outlook for an effective approach to achieve more powerful and more sustainable self-powered systems working with comprehensive ambient weak mechanical energy fitted in diverse application circumstances. Graphical abstract: An ultrasensitive multi-layer triboelectric nanogenerator (TENG) is built for weak ambient energy by a unipolar stacking structure to increase both sensitivity and efficiency. With investigation of mechanical motion in TENG, more energy can be harvested by bringing down the moment of inertia. And a low-loss power management is realized by utilizing the linear region characteristic of an n-type JFET. Highlights: The charge transfer capability in the new device design is increased by at least 50%, and with a theoretical limit of 100%. The first work investigating mechanical motion in TENG theoretically and experimentally. An ultra-simplified linear voltage regulator circuit is specially designed with extremely low power consumption and short start-up time for efficient power management.